2017
DOI: 10.7554/elife.19358
|View full text |Cite
|
Sign up to set email alerts
|

CREB overexpression in dorsal CA1 ameliorates long-term memory deficits in aged rats

Abstract: The molecular mechanisms underlying age-related cognitive deficits are not yet fully elucidated. In aged animals, a decrease in the intrinsic excitability of CA1 pyramidal neurons is believed to contribute to age-related cognitive impairments. Increasing activity of the transcription factor cAMP response element-binding protein (CREB) in young adult rodents facilitates cognition, and increases intrinsic excitability. However, it has yet to be tested if increasing CREB expression also ameliorates age-related be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 72 publications
1
31
1
Order By: Relevance
“…We profiled hippocampal lysates from young and aged wild-type mice and observed a decrease in OGT protein levels, as well as a decrease in global protein O-GlcNAcylation with age ( Figures 1A and 1B). Next, we established a reference point for characteristic hallmarks of hippocampal aging reported to be amenable to brain rejuvenation [26][27][28][29]. First, we assessed the levels of the activated phosphorylated form of the transcription factor CREB (pCREB)-previously demonstrated to underlie improvements in hippocampal-dependent cognitive function in the aged brain [26,29], and whose O-GlcNAcylation status regulates amygdala-dependent memory formation [16].…”
Section: Decreased Ogt Expression and O-glcnacylation Accompany Neuromentioning
confidence: 99%
See 1 more Smart Citation
“…We profiled hippocampal lysates from young and aged wild-type mice and observed a decrease in OGT protein levels, as well as a decrease in global protein O-GlcNAcylation with age ( Figures 1A and 1B). Next, we established a reference point for characteristic hallmarks of hippocampal aging reported to be amenable to brain rejuvenation [26][27][28][29]. First, we assessed the levels of the activated phosphorylated form of the transcription factor CREB (pCREB)-previously demonstrated to underlie improvements in hippocampal-dependent cognitive function in the aged brain [26,29], and whose O-GlcNAcylation status regulates amygdala-dependent memory formation [16].…”
Section: Decreased Ogt Expression and O-glcnacylation Accompany Neuromentioning
confidence: 99%
“…Next, we established a reference point for characteristic hallmarks of hippocampal aging reported to be amenable to brain rejuvenation [26][27][28][29]. First, we assessed the levels of the activated phosphorylated form of the transcription factor CREB (pCREB)-previously demonstrated to underlie improvements in hippocampal-dependent cognitive function in the aged brain [26,29], and whose O-GlcNAcylation status regulates amygdala-dependent memory formation [16]. We detected an agedependent decrease in pCREB ( Figures 1C and 1D) concomitant with decreased expression of cFos ( Figures 1C and 1E), an immediate early gene downstream of CREB also implicated in cognitive rejuvenation [28].…”
Section: Decreased Ogt Expression and O-glcnacylation Accompany Neuromentioning
confidence: 99%
“…The transcription factors cAMP response element-binding protein (CREB) and activating protein 1 (AP-1) are required for plasticity and memory (Alberini, 2009). Ageassociated changes in CREB activity and expression have been reported, and there is compelling evidence indicating that upregulation of CREB levels or activity ameliorates age-related memory deficits (Bach et al, 1999;Yu et al, 2017b). Recently, comparison of the hippocampal transcriptome of young adult and aged mice revealed that AP-1-associated gene expression is also affected during aging (Stilling et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We next investigated whether exposure to an aged hematopoietic system elicits synaptic changes in the hippocampus at a molecular and structural level. Activation of the transcription factor, CREB, via phosphorylation, has been implicated in age‐related cognitive decline and rejuvenation (Villeda et al, 2014; Yu, Curlik, Oh, Yin, & Disterhoft, 2017). Correspondingly, we assessed the levels of CREB phosphorylation (pCreb) and observed a decrease in Het HSC‐reconstituted young mice compared with Iso controls (Figure 1f,g).…”
Section: Introduction Results Discussionmentioning
confidence: 99%